Effects on Recovery of Pediatric Patients Undergoing Total Intravenous Anesthesia with Propofol versus Ketofol for Short-Lasting Laparoscopic Procedures - Ana Nevešćanin Biliškov; Božena Ivančev; Zenon Pogorelić (MDPI AG, 2021)
Background: Combining ketamine and propofol (ketofol) was suggested as a new concept for sedation and general anesthesia in pediatric populations for various conditions. The aim of the present study was to determine the effect of total intravenous anesthesia (TIVA) with propofol and ketofol on recovery after laparoscopic surgery in pediatric patients. Methods: Two hundred children with median age of 5 years who underwent laparoscopic surgery were randomized into two groups. Propofol 1% was used for induction and maintenance of anesthesia in group I, while ketamine-propofol combination (ketofol) was used in group II. Ketamine-propofol combination (ketofol) was prepared in the same applicator for group II. Ketofol ratios of 1:4 and 1:7 were used for induction and maintenance of anesthesia, respectively. A reduced McFarlan infusion dose was used in group I (1.2, 1.0, and 0.8 mL/kg/h for 15, 15, and 30 min, respectively), while a McFarlan infusion dose was used in group II (1.5, 1.3, and 1.1 mL/kg/h for 15, 15, and 30 min, respectively). Extubating time, duration of anesthesia, and length of stay in post-anesthesia care unit (PACU) were recorded. Results: Extubating time was significantly lower in the ketofol group than in the propofol group (240 s vs. 530 s; p < 0.00001). Significantly shorter duration of anesthesia (47 min vs. 60 min; p < 0.00001) as well as length of stay in the PACU (35 min vs. 100 min; p < 0.00001) were recorded in ketofol compared to the propofol group. Total fentanyl (100 µg (interquartile range, IQR 80, 125) vs. 50 µg (IQR 40, 60); p < 0.00001) and propofol (260 mg (IQR 200, 350) vs. 160 mg (IQR 120, 210); p < 0.00001) consumption per body weight were significantly lower in the ketofol group. Conclusions: TIVA with ketamine-propofol combination (ketofol) using a reduced McFarlan dose regimen shortened extubating time, duration of anesthesia, as well as length of stay in the PACU in pediatric anesthesia after laparoscopic surgery.